1998
DOI: 10.1037/0021-843x.107.2.355
|View full text |Cite
|
Sign up to set email alerts
|

Expressed emotion, attributions, and schizophrenia symptom dimensions.

Abstract: Using a sample of 40 Anglo American family members of schizophrenic patients, the present study replicates and lends cross-cultural support for an attribution-affect model of expressed emotion (EE). Consistent with attribution theory, the authors found that highly critical relatives (high-EE) viewed the illness and associated symptoms as residing more within the patient's personal control as compared with less critical relatives (low-EE). A content analysis classified the types of behaviors and symptoms most f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
2
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 20 publications
4
69
2
3
Order By: Relevance
“…Subsequent studies have similarly reported that family members' expression of negative affect (defined as hostility or criticism) was associated with their attributions regarding the patient's negative behavior (e.g. Barrowclough, Johnston, & Tarrier, 1994 ;Lopez, Nelson, Snyder, & Mintz, 1999 ;Weisman, Nuechterlein, Goldstein, & Snyder, 1998). In this research, attributions played a significant role in determining family members' emotional reactions despite the fact that the family members were aware the patient suffered from schizophrenia.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Subsequent studies have similarly reported that family members' expression of negative affect (defined as hostility or criticism) was associated with their attributions regarding the patient's negative behavior (e.g. Barrowclough, Johnston, & Tarrier, 1994 ;Lopez, Nelson, Snyder, & Mintz, 1999 ;Weisman, Nuechterlein, Goldstein, & Snyder, 1998). In this research, attributions played a significant role in determining family members' emotional reactions despite the fact that the family members were aware the patient suffered from schizophrenia.…”
mentioning
confidence: 76%
“…emotional withdrawal) as more controllable than their behavioral excesses (positive symptoms, e.g. hallucinations) (see Weisman, Nuechterlein, Goldstein, & Snyder, 1998). There may be important disability\illness factors that contribute to this differential pattern.…”
Section: Discussionmentioning
confidence: 97%
“…More specifically, critical and/or hostile relatives tend to make more attributions to the personality characteristics of the patient and view the patient's behaviours as more controllable by the patient, whereas emotionally over-involved relatives make more attributions to illness and see behaviours as uncontrollable by the patients (Brewin et al 1991;Harrison and Dadds 1992;Provencher and Mueser 1997). The relationship between internal controllable attributions and criticism/hostility has been noted to be more pronounced for negative symptom behaviours (Barrowclough et al 1994;Weisman et al 1998). Barrowclough and Parle (1997) showed that when relatives are disturbed by the symptoms of illness and when they believe that they cannot cope with symptomatic behaviours their criticism increases.…”
Section: Introductionmentioning
confidence: 91%
“…In those studies, an attribution model of EE (Brewin et al, 1991;Butzlaff and Hooley, 1998) was used and criticism and emotional over-involvement towards the patient were found the key components of EE. Higher levels of criticism were correlated with families' perceptions that patients' problem/behaviours are controllable by the patients themselves (Weisman et al, 1998), while more disturbed behaviour by a schizophrenic patient was perceived as the patient's failure to engage in productive activities King et al, 2003). As described by Leff and Vaughn (1985), emotional over-involvement reflects a set of feelings and behaviour of a family member towards the patient, indicating evidence of over-protectiveness or self-sacrifice, excessive displays of emotion with the use of praise or blame, preconceptions and statements of attitude.…”
Section: Literature Reviewmentioning
confidence: 97%